PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MENGGUNAKAN MODEL LEARNING CYCLE 7E UNTUK MENINGKATKAN KETERAMPILAN PENYELESAIAN MASALAH - Erlina, Nia; Jatmiko, Budi; Raharjo, Raharjo (JPPS (Jurnal Penelitian Pendidikan Sains), 2016)
This study aims to develop physics learning material based on 7E learning cycle model veable to use improving problem solving skills. Implementation of the research has done in class X of SMAN 16 Surabaya academic year 2014/2015. Methods of data collection are validity, tests, observations, and questionnaires. The materials was developed using the modified 4D model of the design testing one group pretest-posttest design. Analysis of the significance of the increase in problem-solving skills using a paired t test while to see the consistency of learning outcomes using analysis of variance. Results from this research showed: 1) the validity of learning material give results of the validation consisted of RPP value of 3.47 is valid categorized, BAS value of 3.50 is valid categorized, LKS is 3.64 categorized very valid, problem solving skills test value of 3 is valid categorized, legibility BAS is 73.90% being categorized, legibility LKS is 77.46 % higher category, the level of difficulty BAS  is 26.52 % low categorized, the difficulty level of LKS is 26.32% low categorized; 2) the practicality of the learning material consist of a feasibility study learning of 93.25% is very well categorized and learning implementation constraints that arise when students understand the steps the experiment; 3) the effectiveness of learning, in terms of problem-solving skills increase significantly between before and after the learning with a high degree of improvement category; Average student activity categorized in three classes, as well as students respond positively to the learning activities, and positive student?s response of learning activity. The results showed that physics learning material based on 7E learning cycle model veable to use improving problem solving skills. Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran fisika model learning cycle 7E yang layak digunakan untuk meningkatkan keterampilan penyelesaian masalah. Penelitian pada kelas X SMAN 16 Surabaya tahun ajaran 2014/2015. Metode pengumpulan data menggunakan validasi, tes, observasi, dan angket. Perangkat pembelajaran dikembangkan menggunakan model 4-D dengan rancangan ujicoba one group pretest-posttest design. Analisis signifikansi peningkatan keterampilan penyelesaian masalah menggunakan uji t berpasangan sedangkan untuk melihat konsistensi hasil pembelajaran menggunakan analisis varians. Hasil penelitian: 1) validitas perangkat pembelajaran dengan hasil nilai validasi terdiri dari RPP sebesar 3.47 berkategori valid, BAS sebesar 3.50 berkategori valid, LKS sebesar 3.64 berkategori sangat valid, tes keterampilan penyelesaian masalah sebesar 3 berkategori valid, keterbacaan BAS sebesar 73.90% berkategori sedang, keterbacaan LKS sebesar 77.46% berkategori tinggi, tingkat kesulitan BAS sebesar 26.52% berkategori rendah, tingkat kesulitan LKS sebesar 26.32% berkategori rendah; 2) kepraktisan perangkat pembelajaran ditinjau dari keterlaksanaan pembelajaran sebesar 93.25% berkategori sangat baik dan kendala pelaksanaan pembelajaran yang muncul saat siswa memahami langkah-langkah percobaan; 3) keefektifan perangkat pembelajaran, ditinjau dari peningkatan keterampilan penyelesaian masalah secara signifikan antara sebelum dan sesudah pembelajaran dengan derajat peningkatan berkategori tinggi; rata-rata aktivitas siswa di tiga kelas berkategori baik, serta respons siswa positif terhadap aktivitas pembelajaran. Hasil penelitian menunjukkan bahwa perangkat pembelajaran fisika model learning cycle 7E layak digunakan untuk meningkatkan keterampilan penyelesaian masalah.